Linking HR formality with employee job quality: The role of firm and workplace size - Storey, David J.; Saridakis, George; Sen‐Gupta, Sukanya; Edwards, Paul K.; Blackburn, Robert A. (Human Resource Management, 2010)
AbstractThe process of managing a small firm differs from managing a large firm, because small firms face distinct forms of risk and organize their human resources differently, often informally (Kotey & Slade, 2005; Storey, 2002). This paper introduces and tests a new variable, self‐reported job quality (SRJQ), as a key link in the causal chain between HR practices and outcomes. In comparing small firms with large ones, we present three key findings: (1) employee reports of job quality are highest in small firms and decrease as firm size increases; (2) in workplaces owned by large firms, job quality is highest in the smallest workplaces; and (3) workers in small workplaces owned by large firms report lower job quality than workers in comparable sized workplaces owned by small firms. Our findings are partially explained by how formally HR practices are implemented. We show that formality increases with firm size and workplace size. Importantly, evidence suggests that employing an HR professional (a key indicator of HR formality) lowers SRJQ in single‐site SMEs. Implications for small business owners, HR professionals in large and small firms, and policy makers are discussed. © 2010 Wiley Periodicals, Inc.